ARAB SPRING: PERUBAHAN REZIM DAN TEGANGAN HUBUNGAN AS – DUNIA ARAB REFLEKSI SOSIO-HISTORIS - Herdi Sahrasad (CMES (Center of Middle Eastern Studies), 2013)
The revolutions in the Arab World  such as Egypt, Tunisia, Marocco, Libya, Syriaand Yemen have affected  political  landscapes  in the Middle East countries. Revolutionsin the MENA countries  have broken up relations between the Arab World and the US.The revolutions also have paved the way for Islamic groups to put  political pressures totake power . Moreover, the Arab Spring have the influence over changes in the UnitedStates foreign policy  in Middle East. But, up to now,  it is not  clear that the revolution in the Middle East in 2011 is agreat opportunity for the U.S. to increase its role in countries. It's not  clear too,  whetheror not  it also a new opportunity for the U.S. to establish strategic alliances in ArabicWorld. While  Washington was surprised by the fall of the regimes of Egypt and Tunisia, for instance, there is  uncertainty  that the two countries  would be the new alliances ofthe US in the near future.  America has lost its loyalists  such as former Egyptian President Hosni Mubarakand Ben Ali, Tunis. But at the same time, the proximity of the the US-Gulf alliances isincreasing, especially with  Saudi Arabia,Bahrain, Kuwait  and Qatar . Washington for awhile is  still groping, if not frenzy, in rebuilding  the present relationship with the MiddleEast, as long as the MENA countries  are still in the era of transition. The U.S  and theWest are aware about  that  problem, and they  understand  that  in the Middle East thepolitical uncertainty  is so apparently.